THE IMPACT OF LEADERSHIP STYLE, WORK MOTIVATION, AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE (BANK BNI KAWANGKOAN BRANCH) - Langi, Stifan (Sam Ratulangi University, 2015)
ABSTRACT There are some factors on the employee performance such as leadership style, work motivation, and job satisfaction. This research is design to analyze the related between leadership style, work motivation, and job satisfaction at Bank Negara Indonesia Kawangkoan Branch. Use the Multiple Regression Analysis Method, so the researcher can analyze the influence of the independent variable to dependent variable, which is employee performance. The independentvariablesare leadership style, work motivation, and job satisfaction. Based on the result on the analysis of data using multiple linear regression analysis techniques, the F test and t test, obtained results which indicate that the style of leadership, motivation and job satisfaction simultaneously significant effect on the performance of employees at Bank BNI Kawangkoan Branch. This partial result shows these three variables are also significant positive effect on the performance of the employee unless the variable motivation. Keywords: leadership style, work motivation, job satisfaction, employee performance